An Analysis of the Cohesion And Coherence Of the Students' Narrative Writings in SMP Negeri 2 Banjar - ., PIPIT OLVA ANDAYANI; ., Prof. Dr.I Ketut Seken,MA; ., Drs. Asril Marjohan,MA (Jurnal Pendidikan Bahasa Inggris Indonesia, 2014)
Pipit Olva Andayani. 2014. An Analysis of the Cohesion and Coherence of the Students? Narrative Writings in SMP Negeri 2 Banjar. Thesis, Department of Language Education, Graduate Program, Ganesha University of Education Thesis. Language Education. Postgraduate Study Program, Ganesha University of Education. Advisors: (I) Prof.Dr.I Ketut Seken, M.A (II) Drs. Asril Marjohan, M.A This study attempted to describe and explain (a) the cohesion of English narrative writings produced by the students under study; (b) the coherence of English narrative writings produced by the students under study; (c) the problems encountered by the students under study in creating cohesion and coherence in their English narrative writing. This study was designed as qualitative study. This study was conducted on 30 students of the ninth grade in SMP Negeri 2 Banjar. The data were collected through students? narrative writings, students? questionnaire and teachers? interview. The data were analyzed by using the theory introduced by Halliday and Hasan (1976). The analysis was concerned with grammatical cohesion (reference, substitution, ellipsis, conjunction), lexical cohesion (reiteration and collocation) and aspect of coherence that were found in the students? writings. The results of this study show that (a) the students were able to use the five types of cohesive devices to make their writing coherent. The first cohesive devices used were reference (70.77%) with personal reference as the dominant use. Then, it was followed by conjunction (28.51%), substitution (0.57%), ellipsis (0.14%). Lexical cohesion was used 137 item dominated with repetition (78%). (b) The students? produced coherence of the narratives through the development of themes, and the generic structure. (c) Some problems of coherence identified were the problems with reference (personal, demonstrative), conjunction (additive, adversative, causal, temporal) and limited choice of lexical item. Kata Kunci : cohesion, coherence, narrative Pipit Olva Andayani. 2014. Analisis Kohesi dan Koherensi Tulisan Narasi Siswa di SMP Negeri 2 Banjar. Tesis Program Studi Bahasa, Pascasarjana, Universitas Pendidikan Ganesha Tesis. Program Studi Bahasa. Pascasarjana. Universitas Pendidikan Ganesha. Pembimbing (I) Prof.Dr.I Ketut Seken, M.A (II) Drs. Asril Marjohan, M.A Penelitian ini bermaksud mendeskripsikan dan menjelaskan (a) penanda kohesi tulisan narasi siswa; (b) koherensi tulisan narasi siswa; (c) masalah kohesi dan koherensi dalam tulisan narasi siswa. Bentuk penelitian ini adalah penelitian kualitatif. Penelitian ini dilakukan pada 30 siswa kelas Sembilan SMP Negeri 2 Banjar. Data diperoleh melalui tulisan narasi siswa, kuesioner siswa dan wawancara guru. Data yang diperoleh dianalis berdasarkan teori Halliday and Hasan (1976). Analisis fokus pada kohesi gramatikal (referensi, substitusi, ellipsis, konjungsi), kohesi leksikal (pengulangan dan kolokasi) dan aspek koherensi. Hasil dari penelitian ini menunjukkan (a) Hasil penelitian ini menunjukkan bahwa (a) siswa pada dasarnya mampu menggunakan lima piranti kohesif untuk membuat tulisan mereka menjadi koherensi. Penanda kohesi yang dimaksud adalah referensi (70,77%) yang didominasi dengan penggunaan referensi personal. Kemudian, diikuti oleh konjungsi (28.51%,) substitusi (0,57%), ellipsis (0,14%). Penggunaan kohesi leksikal 137 butir yang didominasi dengan pengulangan (78%). (b) Koherensi teks narasi diciptakan dengan pengembangan ide utama dari teks itu yang didukung oleh ide setiap paragraf, penggunaan generic structure dari teks narasi. (c) Beberapa masalah dalam koherensi yang diidentifikasi dalam tulisan siswa yaitu menyangkut penggunaan referensi (personal, demonstratif), konjungsi (penambahan, pertentangan, sebab-akibat, urutan) dan pemilihan kata dari butir leksikal.keyword : kohesi, koherensi dan tulisan narasi